Genotoxicity of organic pollutants in source of drinking water on microalga Euglena gracilis - Li, Mei (Ecotoxicology (London, England), 2009)
The potential toxicities of organic pollutants in the drinking water source at Meiliang Bay of Lake Taihu were investigated by comet assay and antioxidant enzyme approach on microalgae Euglena gracilis. The organic extracts of the water samples could induce DNA damage on microalgae cells. Statistically significant differences (P < 0.05) were observed at groups of 0.3x, 3x and 10x concentrations compared with the control and a solvent control (DMSO). The organic extracts also affected antioxidant enzyme activity and induced lipid peroxidation in the microalga. In the high dose group, there was an obvious increase in SOD content (P < 0.05). The results suggest that the concentrated organics from water sample extracts have adversary effects on E. gracilis and could possibly damage the ecosystem